Impacto econômico do episódio da dengue na cidade de Teresina, Piauí, Brasil - Parente, Mírian Perpétua Palha Dias (2014)
Dengue is considered the most important arboviral internationally. An estimated 390 million people infected annually by the dengue virus and about a quarter expressed some level of clinical severity. In the last decade, Brazil has been contributing to the global burden of dengue in the Western hemisphere, despite investments to control the vector mosquitoes and thus attempting to reduce disease transmission. Objective: To analyze the economic impact of dengue episode from the perspectives of the public payer and society, in outpatients and inpatients served in public and private health sectors and realize systematic literature review about dengue costs in the Americas countries. Methods: This is an economic evaluation in health care, using the method of macro and micro costing, which sets up a cost analysis of an episode of dengue among ambulatory and hospital with suspected dengue cases treated in the public and private sectors. Patients were interviewed at the beginning of the episode of dengue and approximately 30 days after the onset of symptoms. Results and discussion: The results presented were based on interviews of 415 patients included in the study. Of the respondents, 355 (85.5%) were ambulatory and 60 (14.5%) of the group of hospitalized group. Considering the perspective of society, the average cost per unit of outpatient care in the public sector was $ 72 and in the private sector was USD 500. For hospitalized cases, the overall average costs for patients treated in the public sector were about four times higher (270 USD), while in the private sector, about 1.5 times higher than ambulatory patients (835 USD). Considering the prospect of paying assessed only the public sector, where the average cost per outpatient ward was USD 31 and USD 198 hospitals was lower than the assessment value from the perspective of society. Conclusion: Dengue is a high cost in the private and public health care economy as well as to society, beyond that costs vary according to the sector of care (outpatient and inpatient).